Meaning Differences in Indigenous Kriya and Crafts in Indonesia and Their Leverage on the Craft of Science Globally - Hendriyana, Husen (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
The meaning of a term is supported by the cultural values of the supporting community, specifically the designer community, who recognize and have faith in the contained values. In a broader sense, the terms kriya and kerajinan are components of the craft-science field. Since 1968, the meaning of the terms kriya, kerajinan, and Craft has been a source of contention among stakeholder community groups in Indonesia. This article aims to convey a scientific understanding of adaptive crafts based on the global development of Indonesian indigenous crafts. This study employed a descriptive-analytical method and an ethnographic communication approach, focusing on sociolinguist studies that include diachronic and synchronic studies. Based on current and relevant theories, the research findings demonstrated the development of Indonesian indigenous crafts in a global context. In conclusion, the Hasta Cipta Preneurship (HCP) theoretical approach was used to identify the basic components: creative ideas, people, products, markets, venues, reproduction, humanists, and support. This HCP creative process extends the definition of new kriya as one of the academic competencies of two-dimensional and/or three-dimensional visual works that advance the conceptual intelligence of Laku Hidup Lestari (LHL– Sustainable Lifestyles) and is oriented to the aspects of utility, significance, and aesthetics, with the goals and targets for achievement to the aspect of user needs, solutions, and innovation.